2015
DOI: 10.2217/nnm.15.111
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Mediated Drug Delivery for Treating Melanoma

Abstract: Melanoma originated from melanocytes is the most aggressive type of skin cancer with limited treatment options. New targeted therapeutic options with the discovery of BRAF and MEK inhibitors have shown significant survival benefits. Despite the recent progress, development of chemoresistance and systemic toxicity remains a challenge for treating metastatic melanoma. While the response from the first line of treatment against melanoma using dacarbazine remains only 5–10%, the prolonged use of targeted therapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 195 publications
0
26
0
Order By: Relevance
“…Strategies to deliver drugs to specific cell types are needed. Some approaches, such as transporter-mediated drug uptake 43 , bi-specific antibodies 44 , and nanoparticle-mediated delivery 45 , require further clinical evaluation.…”
Section: Integrating Knowledge and Keeping Metabolism In Mind When Dementioning
confidence: 99%
“…Strategies to deliver drugs to specific cell types are needed. Some approaches, such as transporter-mediated drug uptake 43 , bi-specific antibodies 44 , and nanoparticle-mediated delivery 45 , require further clinical evaluation.…”
Section: Integrating Knowledge and Keeping Metabolism In Mind When Dementioning
confidence: 99%
“…It is plausible that there is more collagen in normal skin adjacent to DN than in that adjacent to MM because melanoma growth is not only associated with malignant growth of cancer cells, but also changes in its stroma microenvironment to support metastasis. 35 Paidi et al 36 discovered that the use of RS is feasible to detect changes in the stroma of the lung microenvironment in response to primary breast tumors. Sahu et al 37 found that early malignancyassociated changes in normal contralateral sites of oral cancer may lead to anatomical variability and cause misclassification between contralateral and tumor.…”
Section: Journal Of Biomedical Opticsmentioning
confidence: 99%
“…The MSC-mediated oncolytic approach has been used also in experimental melanoma [123] and the potential of MSCs to deliver targeted agents in experimental melanoma has been previously reviewed [124]. An excellent survey of the use of NP-based therapeutics for melanoma treatment does not take in consideration MSCs or other cell-mediated delivery systems [125]. In the light of the strong evidence of magnetic resonance imaging of pulmonary metastases with magnetic NPs/ MSCs [126], tumor targeting with silica NPs/MSCs [127] and photothermal therapy with gold NPs/MSCs [128], it is our opinion that the theranostic use of MSC/NPs in melanoma is near to cross the boundary between the preclinical and the clinical phase.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%